Kontribusi Penggunaan Model Discovery Learning Terhadap Kemampuan Berpikir Kreatif Matematik Peserta Didik - Siska Ryane Muslim (JP3M (Jurnal Penelitian Pendidikan dan Pengajaran Matematika), 2016)
This study aimed to determine a positive contribution of the usage of discovery learning model to the mathematics creative thinking abilities of students and to find out how students’ learning activities by using its model. The method used was experimental research. The population in this study were students of class-VIII SMP. Samples were taken randomly by class. Instruments used were the test of mathematical creative thinking abilities and observation sheets activities. The results showed a positive influence of the usage of discovery learning model to the mathematics creative thinking abilities of students. Students’ learning activities through discovery model were included in active level.